Serum miR-485-5p expression and clinical significance in epilepsy secondary to cerebral infarction - Chai, Qiong; Chen, Xingyin; Min, Li; Li, Haiju; Sun, Yajuan; Bu, Changdan (Folia neuropathologica, 2024)
MicroRNA (miR)-485-5p has been linked to regulation of neurological disorders. The current study examined miR-485-5p levels in patients with epilepsy secondary to cerebral infarction and investigated its predictive significance. The Gene Expression Omnibus (GEO) database was employed to screen differentially expressed miRNAs in cerebral infarction and epilepsy. 168 patients with cerebral infarction were enrolled, including 67 patients with secondary epilepsy and 101 patients without secondary epilepsy. Serum miR-485-5p levels were examined by reverse transcription-quantitative real-time PCR (RT-qPCR). Logistic regression analysis was used to explore risk factors for epilepsy secondary to cerebral infarction. The diagnostic and predictive value of miR-485-5p was evaluated by receiver operating characteristic (ROC) analysis. Bioinformatics predicted miR-485-5p target mRNA and performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. The GEO database identified differentially expressed miRNAs including miR-485-5p. miR-485-5p levels were poorly expressed in patients with cerebral infarction ( p < 0.05) and negatively correlated with the National Institutes of Health Stroke Scale (NIHSS) score, an indicator of cerebral infarction severity. Additionally, miR-485-5p is a typical indicator for differentiating cerebral infarctions from controls. Serum miR-485-5p was lower in patients with epilepsy secondary to cerebral ischemia compared to non-epilepsy patients and is a potential risk factor for epilepsy secondary to cerebral infarction. The sensitivity and specificity for predicting epilepsy were 74.63% and 80.20%, respectively. KEGG pathway studies revealed miR-485-5p's target mRNA is primarily enriched in the adipocytokine signaling pathway and the AMPK pathway. miR-485-5p correlates with cerebral infarction severity. Low expression of miR-485-5p is a promising predictive biomarker for epilepsy secondary to cerebral infarction.